What learning styles do business students use during COVID-19? - Fonseca Romero, Gabriela; Esparza Paz, Fernando; Esparza Zapata, Erika (mktDESCUBRE, 2021)
At present, the world is experiencing a situation of transformation due to the appearance of the Covid-19 pandemic, which forces in all areas to generate substantial changes and mainly in the educational field. Determining the relationship of learning styles and academic performance at the time of Covid-19, in business students is the objective of this study. The article considers a descriptive, non-experimental and transversal investigation, designed with a mixed approach, observing a field data; completed with bibliographic information; study that was carried out in the middle of the confinement period (May-June 2020), which considers data from students enrolled in the academic period September 2019-February 2020, out of a total of 2816 students belonging to five business careers, of the Faculty of Business Administration, Escuela Superior Politécnica de Chimborazo, taking a sample of 338 students. Lynn O`brien’s (1990) preferred learning channel test was the main methodology used to identify the Learning Styles of the student group. The main findings showed that the applied test showed that the students have developed to a lesser or greater degree the three learning styles, that is, auditory (39%), visual (38%) and kinesthetic (23%). It is therefore concluded that the students have considered these three types of styles in their teaching and learning process in the middle of the pandemic and confinement, and it has allowed their performance to be measured, where the classes were developed using virtual education tools.